2020
DOI: 10.1021/acsearthspacechem.0c00013
|View full text |Cite
|
Sign up to set email alerts
|

Antimony Sorption to Goethite: Effects of Fe(II)-Catalyzed Recrystallization

Abstract: The environmental mobility and bioavailability of antimony (Sb) are strongly influenced by sorption to Fe­(III) oxide minerals, such as goethite (αFeOOH). Exposure to aqueous Fe­(II), as occurs, for example, under reducing conditions in soils and sediments, catalyzes the recrystallization of goethite. Herein, we examine, for the first time, the effect of Fe­(II)-catalyzed goethite recrystallization on the sorption of co-associated Sb­(V). The use of an enriched aqueous 57Fe­(II) tracer provided direct evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 82 publications
(244 reference statements)
4
60
1
Order By: Relevance
“…In shooting range soils, EXAFS characterization indicated that Sb (V) was the major species [15]. Macroscopic and spectroscopic characterizations of soils and sediments have suggested that iron oxides, hydroxides, and oxyhydroxides are major sinks for Sb (V) species, and strong associations have been observed [14,16,17]. Consequently, many adsorption studies using pure iron mineral phases have been reported [10][11][12][13][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In shooting range soils, EXAFS characterization indicated that Sb (V) was the major species [15]. Macroscopic and spectroscopic characterizations of soils and sediments have suggested that iron oxides, hydroxides, and oxyhydroxides are major sinks for Sb (V) species, and strong associations have been observed [14,16,17]. Consequently, many adsorption studies using pure iron mineral phases have been reported [10][11][12][13][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Macroscopic and spectroscopic characterizations of soils and sediments have suggested that iron oxides, hydroxides, and oxyhydroxides are major sinks for Sb (V) species, and strong associations have been observed [14,16,17]. Consequently, many adsorption studies using pure iron mineral phases have been reported [10][11][12][13][17][18][19][20]. Macroscopic studies coupled with surface complexation modeling using goethite as a mineral indicate that Sb (V) has strong affinity for goethite and the adsorption is pH-dependent, where Sb (V) retention decreased drastically above pH 6 [10].…”
Section: Introductionmentioning
confidence: 99%
“…The initial component of this trend is consistent with previous work showing that small (<5%) levels of microbial Fe(III) oxide reduction can cause decreased Sb mobility (Burton et al, 2019). This can occur without Sb(III) formation (which appears to require considerably lower Eh than does As(III) formation; e.g., Mitsunobu et al, 2006) via Fe(II)-induced transformation or recrystallization of Sb(V)-bearing Fe (III) oxides, leading to occlusion of Sb(V) within the host Fe(III) oxide structure (Burton et al, 2019(Burton et al, , 2020.…”
Section: Water Resources Researchmentioning
confidence: 99%
“…In addition, microbially mediated reductive dissolution of As‐ or Sb‐bearing host phases (e.g., Fe(III) oxides) can trigger release of As/Sb species into solution (Burton et al, 2008; Fendorf, Nico, et al, 2010; Hockmann, Lenz, et al, 2014; Kocar & Fendorf, 2009; Kocar et al, 2006). While this is a well‐established driver of enhanced As mobility in sediments, recent evidence indicates that partial Fe(III) oxide reductive dissolution can instead cause decreased Sb mobility under reducing conditions (e.g., Burton et al, 2019, 2020). In addition, aqueous thiolated As(III)/(V) and Sb(III)/(V) species have been shown to play increasingly important roles under sulfidic conditions (e.g., Hockmann et al, 2020; Planer‐Friedrich et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al 28 demonstrated the high removal capacity for As using Fe-Zr binary oxide. Being from the same group (group V), As and Sb share some similar properties, but also show contrasting interactions with Fe and organic moeities 29,30 .…”
Section: Introductionmentioning
confidence: 99%